A promoção do engajamento discente por professoras de classe inclusiva e suas relações com processos de estresse e coping docente - Silveira, Kelly Ambrósio (2014)
Teachers in inclusive classes are often subject to work-related stressing factors, where coping strategies can affect their interaction with students with special educational needs (SEN). In face of paucity of studies on these relationships, this investigation, which is based on the Self System Model to Motivational Development, aimed at identifying and analyzing: 1) Stressing factors, level and symptoms of stress in teaching and in inclusive classes, as well as the sense of self -effectiveness and satisfaction at work using a set of scales, some of them specially translated and adapted for 19 female teachers of the 3 first years of elementary education in Vitória, ES, Brazil; 2) coping strategies through interviews with a subgroup of 17 female teachers, with or without symptoms of stress; 3) facilitating behaviors in teaching engagement and disengagement presented by 4 teachers, 2 with symptoms of stress, 2 without, observed during 5 recorded video sessions of 30 minutes for each participant. The study identified stressing factors related mainly to teaching conditions and students' engagement. Adaptive coping was directly correlated to personal and work variables, and inversely correlated to the total of stress symptoms. Stressed teachers reported more stressing demands, negative emotional reactions and poorly-adaptive coping, mainly helplessness; and fewer teaching engagement facilitating behaviors in terms of affective involvement, support to autonomy and structural strengthening. They also presented less flexibilization of classroom rules and higher rejection while in contact with SEN students. This study is expected to provide tools to assessment and psychological intervention for teachers' well-being in inclusive education.